MEAT PRODUCTION BY STEERS OF DIFFERENT GEOTYPES - & et al., Velmatov (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2018)
The objective of this study to investigate  meat production by steers of different genotypes. In order to study the productivity of Simmental and black and white Simmental x Holstein cross bred, steers, six groups of bull-calves with 15 animals each, were formed. The first group consisted of Simmental steers, the second group (3/8) blooded, the third group (1/2) blooded, the fourth group (5/8) blooded, the fifth group (3/4) blooded  and the sixth group (7/8)  blooded Holstein steers respectively. Under the same conditions of feeding and maintenance purebred Simmental animals grow more intensively. At 18-months of age they exceed (3/8) Holstein blooded bull calves by 6.2 kg, half blooded by 16.5 kg, (5/8) blooded by 18.4 kg, (3/4) blooded by 25 kg  and (7/8) blooded by 35.2 kg (Р